Krankheitsassoziierte, patientenbezogene und therapiebedingte Komplikationen beim multiplen Myelom - Rapi, Aikaterini; Hampel, Mareike; Mai, Elias K.; Goldschmidt, Hartmut (Die Onkologie, 2025)
Multiple myeloma (MM) is a complex heterogeneous disease that occurs predominantly in older patients with comorbidities and frailty. Although advancements in treatment have turned MM into a chronic disease for most, disease-associated, patient-specific, and/or treatment-related complications continue to pose significant challenges. The rapid development of new therapies with diverse modes of action has increased the complexity of treatment and requires balancing of efficacy against tolerability. Continuous monitoring of patients with MM is essential to enable early detection of comorbidities and side effects, thereby improving quality of life and preventing or minimizing organ damage. A comprehensive evaluation of patients before initiating treatment is crucial for determining treatment intensity. Treatment options are primarily classified based on the patient's status as "frail vs. fit." Long-term data from clinical studies and registries are needed to better understand and manage rare or late-onset toxicities, such as secondary malignancies. Therefore, improving outcomes for patients with MM remains the key goal.
Gesehen am 28.03.2025